THE INFLUENCING FACTOR OF PURCHASING ECOLOGICAL PRODUCTS: LET'S THINK GREEN - W.M.N, Mohd Nazdrol; M.S, Che Rusuli; A.N., Nabila (Journal of Technology Management and Business, 2016)
The purpose of the research was to examine what the factors that influence purchasing behaviour towards ecological product among Universiti Malaysia Kelantan students. From the research, the researcher has collected primary data and the secondary data that related to the problems of research. In this study, quantitative approach was used and 346 respondents have been selected from Universiti Malaysia Kelantan students. The questionnaires were distributed to the Universiti Malaysia Kelantan students to gather the necessary information. After all data has been collected, the researcher analyzes data using SPSS and interpreted in the diagrams view. Based on the study that has been conducted, the result shows that the most significant factor that influencing purchasing behaviour towards ecological product among Universiti Malaysia Kelantan students are environment concern, awareness about green product and benefit to user but the not significant factor is awareness about price.